A Study on Impact of Political Advertisements on Young Adults (International Journal of Innovative Research in Engineering & Management, 2021)
Ever since a decade, political advertisements are having a  huge influence on voting behavior of younger and older  people across the globe. These political advertisements  through various mediums focus on persuading people in  making their preferences (in choosing their representatives).  This paper examines the impact of political advertisements on  youth, with a sample size of 40 respondents, consisting Under Graduate and Post-Graduate students (age group 19-25), and  their susceptibility to various political advertisements with  respect to the voting behavior. The study area is Bangalore  and the data is collected from the students pursuing their  graduation and post-graduation in Jain University and the  students for the sample study are chosen using simple random  sampling method. Our findings extend the understanding of  the effects of political advertisements on the voting behavior  of Under-Graduate and Post-Graduate students with the help  of cognitive and behavioral psychology. The results are mixed  with respect to the influence made by political advertisements  on youth. But specifically, with the emergence of political  advertisements through new media, the impact has increased  significantly. This study gives new direction for future studies  in order to understand the psychology of youngsters.
Keywords: Advertisements; Media; Politics; Voting behavior; Young adults